“Hi, r u there?” Adventures in Chat Reference Librarianship. - Dodge, Heather (Public Services Quarterly)
The Future Voices in Public Services column is a forum for students in graduate library and information science programs to discuss key issues they see in academic library public services, to envision what they feel librarians in public service have to offer to academia, to tell us of their visions for the profession, or to tell us of research that is going on in library schools. We hope to provide fresh perspectives from those entering our field, in both the United States and other countries. Interested faculty of graduate library and information science programs who would like their students' ideas represented in these pages are invited to contact Nancy H. Dewald at nxd7@psu.edu. Heather Dodge is a recent graduate of Long Island University's Palmer School of Library and Information Science and has completed an additional Master's degree in Humanities and Social Thought from NYU's Draper Program for Humanities and Social Thought. In this column, she discusses the effective development of chat reference competencies. The ALA-Accredited Palmer School of Library and Information Science was established in 1959 at Long Island University's (LIU) Post campus. Palmer's mission is to empower information professionals through education, research and achievement. The Palmer School offers a Doctorate in Information Studies; the Master of Science in Library and Information Science with optional concentrations in Archives and Records Management, Rare Books and Special Collections; Advanced Certificates in both Archives and Records Management and in Public Library Administration. The School also offers a Masters in Science in School Library Media. The Archives and Records Management certificate can be taken post-Master's or concurrently as part of the MSLIS program and is now offered both face-to-face and online.